Characteristics of Urban Heat Island in Pare-Pare City: Insights From Spatial Analysis - Utami, Rahmi Diah; Sideng, Uca; Yusuf, Muhammad; Nasrul , Nasrul; Nur, Medar M.; Hasja, Aulia Diar; Maru, Rosmini (Universitas Hasanuddin, 2024)
This research focuses on understanding the characteristics of the Urban Heat Island (UHI) phenomenon in Parepare City, Indonesia, and its relationship with vegetation density and land surface temperature. The study utilizes satellite imagery data from 2014 and 2021 to analyze the spatial distribution of land surface temperature and vegetation density. The results show a significant negative correlation between vegetation density and land surface temperature, indicating that an increase in vegetation density can contribute to lowering the land surface temperature and mitigating the UHI effect. The findings also emphasize the importance of green open spaces in maintaining a balance of vegetation and preventing a drastic increase in UHI. However, challenges such as land conversion and high population density in the city center pose threats to vegetation preservation. Sustainable land management practices and urban greening initiatives need to be implemented to address these issues. The research concludes that by prioritizing these measures, Parepare City can effectively mitigate the UHI effect and enhance the urban environment's quality and livability.